MODERN SOCIETY BUILDING THROUGH HIGHER EDUCATION IN LITHUANIAN AFTER 1918 - Maumevičienė, Dainora; Maksvytytė, Jūratė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The development of the modern state of Lithuania after the declaration of independence on February 16th, 1918 triggered many changes both in the development of the state and processes related to modern society building. Education and the opening of modern university in Lithuania was closely related to historical, social and political changes. The occupation of Vilnius and the transfer of the most important state governing and state developing institutions to Kaunas as the temporary capital of Lithuania was closely related to the establishment of Lithuanian University in Kaunas in 1922. The society was also impacted by the socio-historical context since some members of the society took an active part processes of the emergence of the Lithuanian University as the establishment of modern system of higher education in Lithuania. Taking into consideration not only the historical context and the approaching celebration of one hundred years of the opening of modern Lithuanian University in Kaunas in 2022, this article aims to discuss processes, factors and context that made prerequisites for the development of modern university in Lithuania in Kaunas in 1922 that, in turn, influenced the development of modern society and nation with a specific focus on its identity.